2005
DOI: 10.1002/adsc.200505089
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Asymmetric Mukaiyama Aldol Reaction Catalyzed by Chiral Gallium Lewis Acid with Trost‐Type Semi‐Crown Ligands

Abstract: Chiral ligand 1a[1] is a known compound. Charaterization data of other chiral ligands (1c-h) are as follows: [2] : A light yellow solid, mp: 90-92 o C. Ligand (S,S)-1c[α] D = +48.0 (c 1.0, CH 2 Cl 2 ). IR ν = 3416, 3058, 2964, 1471, 1449, 1377, 1268, 1217, 1004, 870, 767, 748, 703 19.5, 23.7, 24.1, 29.9, 31.7, 33.7, 55.1, 58.0, 70.1, 79.2, 123.4, 124.5, 124.7, 124.8, 125.4, 125.7, 126.0, 127.0, 127.5, 127.8, 127.9, 128.3, 128.8, 132.2, 133.2, 133.3, 140.7, 143.9, 144. 23.8, 24.3, 29.1, 32.7, 33.7, 54.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 37 publications
(16 reference statements)
1
24
0
Order By: Relevance
“…Consequently, the Lewis-acidic and water-tolerant features of lanthanide(III) salts have aroused much interest in aqueous lanthanide-catalyzed bond-forming reactions [ 1 , 2 , 3 , 4 , 5 , 6 ]. We are studying the Mukaiyama aldol reaction between a silyl enol ether and an aldehyde because this reaction can be both water-tolerant and stereoselective, making it an important carbon–carbon bond-forming reaction ( Figure 1 ) [ 3 , 4 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the Lewis-acidic and water-tolerant features of lanthanide(III) salts have aroused much interest in aqueous lanthanide-catalyzed bond-forming reactions [ 1 , 2 , 3 , 4 , 5 , 6 ]. We are studying the Mukaiyama aldol reaction between a silyl enol ether and an aldehyde because this reaction can be both water-tolerant and stereoselective, making it an important carbon–carbon bond-forming reaction ( Figure 1 ) [ 3 , 4 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, Ga(OTf) 3 with chiral Trost‐type semicrown ligand 39 115 was discovered to be an efficient catalyst for asymmetric Mukaiyama aldol reactions in aqueous media (Scheme ) 116. UV‐vis titration and ESI‐MS analysis confirmed this gallium complex to be a 1:1 complex 117. Control experiments performed without the ligand suggested that it played a key role in accelerating the reaction and suppressing the hydrolysis of the silicon enolates.…”
Section: Asymmetric Catalysts In Aqueous Media and Watermentioning
confidence: 84%
“…In 2002, Ga(OTf) 3 with chiral Trost‐type semi‐crown ligand L8 [ 35] was reported as an efficient catalyst for asymmetric Mukaiyama aldol reactions in aqueous media . The substrate scope was relatively wide and included thioketene silyl acetals, although the use of aliphatic aldehydes led to a significant loss of enantioselectivity . Chiral catalysts formed with Zn(OTf) 2 and i Pr‐pybox ligand L9 or FeCl 2 and hydroxymethyl‐pybox ligand L10 were also reported for asymmetric Mukaiyama aldol reactions in aqueous media.…”
Section: Highlightsmentioning
confidence: 99%